An Economic Model of Patent Exhaustion - Olena Ivus; Edwin L.-C. Lai; Ted Sichelman (Center for Economic Studies and ifo Institute (CESifo), 2017)
The doctrine of "patent exhaustion" implies that the authorized sale of patented goods "exhausts" the patent rights in the goods sold and precludes additional license fees from downstream buyers. This paper offers the first formal economic model of domestic patent exhaustion that incorporates transaction costs in consumer licensing, and examines how a shift in patent policy from absolute to presumptive exhaustion, in which the patent owner can opt- out of exhaustion via contract, affects social welfare. The results show that when transaction costs are low, presumptive exhaustion is socially optimal, because it allows welfare-enhancing price discrimination via downstream licensing. Conversely, when transaction costs are high, the regime of presumptive patent exhaustion leads to a greater loss of static efficiency, because transaction cost frictions offset the benefits of price discrimination, but dynamic benefits in promoting ex ante investment in product quality may outweigh any static inefficiencies.
Keywords: F10; O31; 330; intellectual property; patent exhaustion; first sale doctrine; patent licensing